Gas pressure evolution characteristics of deep true triaxial coal and gas outburst based on acoustic emission monitoring - Xin Zhang; Jupeng Tang; Honghao Yu; Yishan Pan (Scientific Reports, 2022)
Abstract Coal and gas outburst is one of the geological disasters that seriously threaten the safety of coal mines production. In recent years, with the increase of mining depth, outbursts become frequent. To further explore the occurrence mechanism of deep coal and gas outburst, a self-developed true triaxial coal and gas outburst simulation device was used to simulate the coal and gas outburst at different depths. The results show that with the increase of simulation depth, the critical gas pressure of outburst gradually decreases, and the unit outburst intensity increases sharply. The gas threshold of deep coal and gas outburst is lower. During the incubation and excitation, gas pressure has three special variation rules, namely self-increasing characteristic, stage and instantaneous. In the early incubation, acoustic emission (AE) energy is at a low level, low energy frequency is dominant; in the later incubation, AE energy increases greatly, high energy frequency is dominant. From the perspective of AE energy, a quantitative index that reflects the danger of coal and gas outburst in the incubation is defined, which provides a scientific reference for the prediction and prevention of disasters of coal and gas outburst in deep mining.